PIDANA PENGAWASAN TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM DALAM SISTEM PEMIDANAAN DI INDONESIA - Suwarsa, I Putu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
ABSTRACT This research was conducted with the normative approach legislation. Factual approach, analytical approach to the legal concept of a comparative approach in the criminal judicial oversight of Children in Conflict with the Law in the criminal sistem in Indonesia. In formulating criminal law criminal policy oversight of Children in Conflict with the Law in the guidance sistem of positive law in Indonesia, consists of 3 major topics: First, the substance of Children in Conflict with the Law into law in Indonesia, Second, Determination of sanctions / penalties against Children in Conflict with the Law in Indonesia's criminal law policy, Third, criminal oversight of Children in Conflict with the Law and its relevance to the theory of punishment in modern criminal law in Indonesia. Criminal oversight of Children in Conflict with the Law as the integrative goals of punishment in accordance with the ideas and correctional sistem discussed 3 subjects namely: First, criminal oversight of anal naughty review of aspects of the integrative theory of punishment, Second, Criminal oversight of Children in Conflict with the Law review of aspects of correctional sistem, Third, Criminal oversight of Children in Conflict with the Law in terms of aspects of legal protection and benefit of the criminal law requirement for social welfare (children). And its application by all law enforcement components and related institutions involved in handling cases of children in conflict with the law in coaching children in prison.
Keywords: Probation; Children in Conflict with the Law; Punishment Sistem